Effectiveness of Acupressure at PC6 versus ST36 Points on Nausea and Vomiting in First-Trimester Pregnant Women: A Quasi-Experimental Study - Tirtawati, Gusti Ayu; Somoyani, Ni Ketut; Erawati, Ni Luh Putu Sri; Yuniartis, Putri; Nasution, Siti Rahmadani (Media Publikasi Cendekia Indonesia, 2025)
The high incidence of nausea and vomiting during pregnancy, which affects 60-80% of primigravidas and 40-60% of multigravidas in Indonesia, can lead to complications such as dehydration and malnutrition if not managed effectively. This can have a negative impact on maternal health and fetal development. While pharmacological treatments are available, non-pharmacological interventions such as acupressure are gaining attention as a safe and effective alternative. This study aimed to determine and compare the effectiveness of acupressure at PC6 and ST36 points in reducing nausea and vomiting among first-trimester pregnant women. A comparative quasi-experimental design was used with a total sample of 50 pregnant women, divided into two groups: one receiving acupressure at PC6 and the other at ST36. The severity of nausea and vomiting was measured using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) questionnaire before and after the intervention. The results showed a significant decrease in nausea and vomiting scores in both groups (p < 0.001). The mean score reduction was 6.64 in the PC6 group and 6.32 in the ST36 group. Statistical analysis indicated no significant difference between the two groups, suggesting comparable efficacy (p = 0.214). These findings suggest that acupressure at both PC6 and ST36 points is an effective non-pharmacological method for managing nausea and vomiting in early pregnancy. Thus, ST36 can be considered a viable alternative point for treatment